2022
DOI: 10.1002/cam4.5029
|View full text |Cite
|
Sign up to set email alerts
|

Membranous and nuclear staining of CLDN18 in HPV‐independent and HPV‐associated endocervical adenocarcinomas

Abstract: Objectives: A classification system for endocervical adenocarcinoma (ECA) based on high-risk human papillomavirus (HPV) status has been established; however, the immunohistochemical markers distinguishing HPV-independent and HPV-associated ECAs have not been fully described. Here, we aimed to characterize ECA immunopathological features. Methods:We evaluated the immunohistochemical profile of CLDN18, CDX2, PAX8, p16, p53, and CEA in 60 ECAs comprising 10 HPV-independent ECAs and 50 HPV-associated ECAs. Both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Of note is the CLDN18 claudin gene which showed a generally high level of over-expression. High CLDN18 expression was recently reported in certain cervical adenocarcinomas [ 34 ]. Here, we show that it is generally over-expressed in all endometrial cancers, which agrees with previous conclusions [ 34 ] that it could serve as a molecular marker for ECs.…”
Section: Resultsmentioning
confidence: 99%
“…Of note is the CLDN18 claudin gene which showed a generally high level of over-expression. High CLDN18 expression was recently reported in certain cervical adenocarcinomas [ 34 ]. Here, we show that it is generally over-expressed in all endometrial cancers, which agrees with previous conclusions [ 34 ] that it could serve as a molecular marker for ECs.…”
Section: Resultsmentioning
confidence: 99%
“…24 One study showed membranous claudin-18 expression in all gastric-type cervical adenocarcinomas tested (eight of eight cases), but also in a subset of other cervical adenocarcinomas, both HPV-associated and HPV-independent (20 of 52 cases), particularly those with intestinal-type differentiation (five of nine cases positive). 25 This marker also shows potential as a therapeutic target. 25 It can be summarised that, although a combination of markers may help establish gastric differentiation, no marker is totally sensitive or specific and a single reliable marker of gastric differentiation has not yet been identified.…”
Section: Gastric-type Adenocarcinomamentioning
confidence: 99%
“…25 This marker also shows potential as a therapeutic target. 25 It can be summarised that, although a combination of markers may help establish gastric differentiation, no marker is totally sensitive or specific and a single reliable marker of gastric differentiation has not yet been identified.…”
Section: Gastric-type Adenocarcinomamentioning
confidence: 99%
See 1 more Smart Citation